The Social Support, Maternal Stress, and Social-Emotional Development of Preschool Children among Working Mothers’ Family during COVID-19: Social Support, Maternal Stress, and Social-Emotional Development of Preschool Children among Working Mothers’ Family during COVID-19 - Hadlirah Aulia Qudsi; Risda Rizkillah; Alfiasari (Journal of Family Sciences, 2023)
The COVID-19 pandemic has caused many changes that have forced working mothers to adapt. This is more challenging if working mothers have preschool children. This study aimed to analyze the effect of social support and maternal stress on the social-emotional development of preschool children among working mothers’ families during the COVID-19 pandemic. This study involved 70 mothers who worked formally or informally, had children aged 4-6 years, came from intact families, and were domiciled in DKI Jakarta and West Java. Sample selection was made by voluntary sampling, and data were collected self-administered using an online questionnaire. Based on the independent sample T-test, there was no significant difference between formal and informal working mothers on social support, maternal stress, and children's social development. The regression test results showed that social support could improve children's social-emotional development. Conversely, maternal stress can reduce children's social-emotional development. Another finding is that girls have better social-emotional development than boys. The study results have implications that working mothers must have good stress management and coping strategies so that children's social development can develop properly.